Massif long-term strength prediction for geological composite structure - MASLOV, B.; LIASHENKO, Ya.; MAKSYMENKO, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The nonlinear model of multi-component geological environment which depends on the presence of the cracks and fluid saturation is examined. On the example of numerical quantitative analysis of viscous and elastic field parameters near geometrical and material concentrators, like as underground metro passage, the statistical analysis of the forecast results' correspondence to experimental data has been done. Work is a continuation of author's research of creation the reliable model base for computer forecasting of evolution and geodynamic fields in the environments of difficult structure.